2016
DOI: 10.3389/fphys.2016.00576
|View full text |Cite
|
Sign up to set email alerts
|

More Severe Insomnia Complaints in People with Stronger Long-Range Temporal Correlations in Wake Resting-State EEG

Abstract: The complaints of people suffering from Insomnia Disorder (ID) concern both sleep and daytime functioning. However, little is known about wake brain temporal dynamics in people with ID. We therefore assessed possible alterations in Long-Range Temporal Correlations (LRTC) in the amplitude fluctuations of band-filtered oscillations in electroencephalography (EEG) recordings. We investigated whether LRTC differ between cases with ID and matched controls. Within both groups, we moreover investigated whether indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 50 publications
2
26
0
1
Order By: Relevance
“…Differences in signal power and signal-to-noise ratio may potentially also help to reconcile some perhaps contradictory findings. In a recent study, larger LRTCs associated with higher insomnia complaints were observed within groups of insomnia patients and control subjects and interpreted as a sign of being closer to criticality 51 . Interestingly, no LRTC differences were observed between control and insomnia patient groups.…”
Section: Discussionmentioning
confidence: 91%
“…Differences in signal power and signal-to-noise ratio may potentially also help to reconcile some perhaps contradictory findings. In a recent study, larger LRTCs associated with higher insomnia complaints were observed within groups of insomnia patients and control subjects and interpreted as a sign of being closer to criticality 51 . Interestingly, no LRTC differences were observed between control and insomnia patient groups.…”
Section: Discussionmentioning
confidence: 91%
“…Insufficient activation of the subcortical caudate nucleus of the brain is considered key to hyperarousal (Stoffers et al 2014 ) and has been consistently reported in fMRI studies in ASD (Turner et al 2006 ). A recent post-mortem study in ASD (Adorjan et al 2017 ) suggested involvement of reduced caudate interneuron density in the excitation/inhibition disbalance—also implicated in insomnia (Colombo et al 2016a , b ; Van der Werf et al 2010 ). Next to the involvement of subcortical structures, individual differences in brain connectivity have also been implicated in one’s typical quality of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia has also been found to be related to LRTCs. Individuals who experienced worse sleep quality tended to have stronger LRTCs during wakefulness ( Colombo et al, 2016 ). Furthermore, the LRTCs could be controlled by engaging an intrinsic neuroregulation through a closed-loop neuro-feedback stimulation–the LRTCs were found to be stronger during stimulation ( Zhigalov et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…(3) The fluctuation function F ( l ) and window length l were transformed into a logarithmic coordinate, and LSM was used to estimate the linear trend and slope α of the fitted line. α is also commonly referred to as the Hurst scaling exponent H ( Colombo et al, 2016 ) or the DFA exponent ( Krzeminski et al, 2017 ). The DFA exponent of the original EEG was abbreviated as DFAE original .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation